Pengaruh Job Autonomy terhadap Innovative Work Behaviour dengan Work Engagement sebagai Variabel Mediasi pada Karyawan Perusahaan Advertising di Kota Padang - Habby Guna Pratama; Syahrizal (Lembaga Yasin AlSys, 2026)
Innovative work behaviour is a strategic necessity for advertising companies because the nature of their work demands creativity, speed, and the ability to generate new solutions. However, research integrating job autonomy, work engagement, and innovative work behaviour within the context of the advertising industry in Padang City remains limited. This study aimed to analyze the effect of job autonomy on innovative work behaviour, both directly and indirectly through work engagement as a mediating variable. The study employed a quantitative approach with a causal design and involved 50 employees from 10 advertising companies in Padang City, selected using total sampling. Data were collected using a Likert-scale questionnaire and analyzed through partial least squares structural equation modeling (PLS-SEM) using SmartPLS 4. The results showed that job autonomy had positive and significant effects on innovative work behaviour (β = 0.577; p < 0.001) and work engagement (β = 0.536; p < 0.001). Furthermore, work engagement had a positive and significant effect on innovative work behaviour (β = 0.424; p = 0.007) and significantly mediated the effect of job autonomy on innovative work behaviour (β = 0.227; p = 0.011). These findings reinforce the perspective of Job Demands–Resources Theory by demonstrating that job autonomy can promote innovative work behaviour both directly and through increased work engagement. Practically, advertising companies need to provide job autonomy proportionally and create conditions that strengthen work engagement to optimize employees’ innovative behaviour.